Analysis of the Seismic Performance of Site-Bolted Beam to Column Connections in Modularized Prefabricated Steel Structures - Xuechun Liu; Xiaoxiong Cui; Zhiwei Yang; Xinxin Zhan (Advances in Materials Science and Engineering)
This paper proposes a site-bolted connection that is suitable for modularized prefabricated steel structures. Excellent ductility is achieved by various structural measures. Six connection specimens with different parameters were subjected to quasi-static loading tests and finite element analysis (FEA) to determine the seismic performance of the proposed connection (e.g., hysteretic behavior, skeleton curve, ductility, and failure mode). The results of the tests and FEA showed that the connection underwent sufficient plastic deformation under cyclic loading and that its ultimate rotation angle could reach 0.09 rad. A clear plastic hinge formed on the beam before the connection failed, which suggests a ductile failure mode. The connection exhibited a wide hysteresis loop, which indicated good seismic performance. The results also showed that the connection does not slip under small earthquakes and could dissipate energy through slippage in the connection region under a moderate earthquake and through slippage in the connection region as well as plastic deformation at the beam end under a severe earthquake. The number of bolts was the main parameter that affected the seismic performance of the connection. The test and FEA results demonstrated that all six specimens had excellent seismic and ductile performance and an exceptional plastic rotation capacity.